(untitled) (Experimental biology, 2015)
The experimental data significantly enrich scientific information on mechanisms of sheep adaptation to the breeding zones, and enable to discover more deeply the role of the blood system to provide adaptive responses of the organism to environmental conditions. The resulting experimental data can be used to assess the physiological adaptive capacity of sheep. In degeres sheep with semi-coarse wool and pale gray fleece and with semi-thin wool of 48 and 50 -quality the biochemical blood composition is notable for evident stability, reflecting their better adaptability to the conditions of the breeding zone as compared with the other populations of this breed